Lactate Thresholds and the Simulation of Human Energy Metabolism: Contributions by the Cologne Sports Medicine Group in the 1970s and 1980s - Wackerhage, Henning; Gehlert, Sebastian; Schulz, Henry; Weber, Sebastian; Ring-Dimitriou, Susanne; Heine, Oliver (Frontiers in Physiology, 2022)
Today, researchers, practitioners and physicians measure the concentration of lactate during a graded exercise test to determine the anaerobic threshold as a sensitive measure of endurance capacity. In the 1970s and 1980s, a group of Cologne-based researchers around Wildor Hollmann, Alois Mader and Hermann Heck developed the methodology for systematic lactate testing and proposed the concept of a fixed 4 mmol.L-1 lactate threshold (or aerobic-anaerobic transition). Later, they also developed the concept of the maximal lactate steady state (abbreviated as MLSS or maxLass) and designed a sophisticated mathematical model of human energy metabolism during exercise which implements maximum oxygen uptake (VO2max) and maximal rate of glycolysis or maximal rate of lactate generation (Lamax), as two major hallmarks of energy metabolism. Unfortunately, several key papers of this group were only published in German. As a result, major contributions are under-appreciated in the English-speaking world. Mader’s model suggests that the maximal rate of glycolysis (Lamax) can reduce the anaerobic threshold and endurance performance but is vital for excellent exercise performance with higher intensities. It also suggests that the rate of fat oxidation can be expressed as the difference between glycolytic pyruvate synthesis and the actual rate of pyruvate oxidation. This narrative review discusses key contributions of the Cologne group for the development of lactate threshold testing and evaluation. We also describe the impact of Mader’s model of human energy metabolism for a more detailed evaluation of a lactate threshold and a different perspective for human exercise performance.